Simulación numérica mediante el método de elementos discretos de fibras ancladas en suelos granulares (2021)
The inclusion of fibers in the soil as a reinforcing material has become an efficient technique and increasingly used in the field of geotechnical engineering. In order to improve the mechanical properties of the soil, various experimental investigations are focused on studying the response of the system to the variation of the characteristics of the fiber. The contact dynamics method allows us to mathematically simulate the behavior of a material of a divided nature like granular soils. This work highlights the ability of a tool such as LMGC90 to analyse geotechnical problems, specifically the analysis of the addition of fibers to granular soils.